Gender Differences in Somatic Symptoms and Current Suicidal Risk in Outpatients with Major Depressive Disorder - Jeon, Hong Jin; Woo, Jong-Min; Kim, Hyo-Jin; Fava, Maurizio; Mischoulon, David; Cho, Seong Jin; Chang, Sung Man; Park, Doo-Heum; Kim, Jong Woo; Yoo, Ikki; Heo, Jung-Yoon; Hong, Jin Pyo (Psychiatry investigation, 2016)
Although somatic symptoms are common complaints of patients with major depressive disorder (MDD), their associations with suicide are still unclear. A total of 811 MDD outpatients of aged between 18 to 64 years were enrolled nationwide in Korea with the suicidality module of the Mini-International Neuropsychiatric Interview (MINI) and the Depression and Somatic Symptom Scale (DSSS). On stepwise regression analysis, current suicidality scores were most strongly associated with chest pain in men, and neck or shoulder pain in women. Severe chest pain was associated with higher current suicidality scores in men than in women, whereas severe neck or shoulder pain showed no significant differences between the genders. In conclusion, MDD patients of both sexes with suicidal ideation showed significantly more frequent and severe somatic symptoms than those without. Current suicidal risk was associated with chest pain in men, and neck or shoulder pain in women. We suggest that clinicians pay attention to patients' somatic symptoms in real world practice.